Telomere length and ischaemic stroke in women: a nested case–control study. Issue 7 (21st March 2013) - Schürks, M.; Prescott, J.; Dushkes, R.; De, I.; Rexrode, K. M.
<x xml:space="preserve">Abstract</x> Background and purpose Telomere shortening has been implicated in cardiovascular disease (CVD). However, prospective data on the association between relative telomere length (RTL) and ischaemic stroke are scarce and inconclusive. Methods We used a nested case–control design among women participating in the prospective Nurses' Health Study. Participants provided blood samples in 1990 and were followed till 2006. Women with confirmed incident ischaemic stroke were matched to controls by age, smoking, postmenopausal status and postmenopausal hormone use. Quantitative polymerase chain reaction was used to determine RTL in genomic DNA extracted from peripheral blood leukocytes. Conditional logistic regression was used to determine the risk of ischaemic stroke associated with RTL, using RTL quartiles and as dichotomous according to the median. Results Data on RTL were available from 504 case–control pairs. Results did not suggest an association between RTL and ischaemic stroke. The odds ratio (OR) for ischaemic stroke was 0.82 [95% confidence interval (CI) 0.52–1.32] comparing lowest with the highest RTL quartile and 0.90 (95% CI 0.65–1.24) comparing RTL below the median with RTL above the median. Associations were unchanged after additional adjustment for cardiovascular risk factors. Further analyses suggested an association between RTL and fatal ischaemic stroke (54 case–control pairs; lowest versus highest quartile OR = 1.99, 95%CI 0.26–14.9); however, results were statistically insignificant. Conclusion In this large nested case–control study among women RTL was not associated with ischaemic stroke. In light of the varying study results in the literature on the association between telomere length and stroke, additional research is warranted.